Death anxiety, resilience, and family cohesion in parents of children and adolescents in the end stages of life - Mohammadi, Fateme; Zahra Masoumi, Seyedeh; Oshvandi, Khodayar; Bijani, Mostafa; Nikrouz, Leila (Frontiers in Psychology, 2023)
Purpose: Adolescents in the end stages of life impose a lot of psychological stress on other family members, which may affect their resilience and quality of life. So, the aim of the present study was to investigate death anxiety, family adaptability and cohesion, and resilience in the parents of children and adolescents who were at the end stages of life. Methods: This is a cross-sectional study. 210 parents selected by convenience sampling and completed the questionnaires such as demographics survey, the death anxiety scale, connor- davidson resilience scale, family adaptability and cohesion scale. Data were analyzed by descriptive statistics (frequency, percentage, mean and standard deviation), independent t-test, ANOVA and multiple linear regression. The significance level was set at P<0.05. Result: The findings showed that death anxiety in parents of children and adolescents in the end stages of life has a significant inverse correlation with family adaptability and cohesion (p<0.001, r=-0.92) and resilience (p<0.001, r=-0.90). The variables of family adaptability and cohesion, resilience, number of children, the children's illness duration, and marital status can predict 61.34% of the death anxiety variance in these parents. Conclusion: The parents of children and adolescents in end stages of life reported high death anxiety and moderate family adaptability and cohesion, but low resilience. Accordingly, pediatric nurses and healthcare policy makers should develop comprehensive support plans for these parents to facilitate their adaptation and increase their family adaptability and cohesion.